Northen Lights Scottish Dance Theatre - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Scottish Dance Theatre, 21 years old this year, has thrived during the past decade under the directorship of Jane Smith. PALABRAS CLAVE: DOG, Liv Lorent, Hofesh Shechter's, Luxuria